When you look like us - Harris, Pamela N. (Quill Tree Books, an imprint of HarperCollins Publishers, 2021)
When you look like us--brown skin, brown eyes, black braids or fades--everyone else thinks you're trouble. No one even blinks twice over a missing black girl from public housing because she must've brought whatever happened to her upon herself. I, Jay Murphy, can admit that, for a minute, I thought my sister Nicole just got caught up with her boyfriend--a drug dealer--and his friends. But she's been gone too long. Nic, where are you? If I hadn't hung up on her that night, she would be at our house, spending time with Grandma. If I was a better brother, she'd be finishing senior year instead of being another name on a missing persons list. It's time to step up, to do what the Newport News police department won't. Bring her home --